Engineered nanomaterials: from their properties and applications, to their toxicity towards marine bivalves in a changing environment - De Marchi, Lucia (2019)
As a consequence of their unique characteristics, the use of Engineered Nanomaterials (ENMs) is rapidly increasing in industrial, agricultural products, as well as in environmental technology. However, this fast expansion and use make likely their release into the environment with particular concerns for the aquatic ecosystems, which tend to be the ultimate sink for this type of contaminants. Considering the settling behaviour of particulates, benthic organisms are more likely to be exposed to these compounds. In this way, the present review aims to summarise the most recent data available from the literature on ENMs behaviour and fate in aquatic ecosystems, focusing on their ecotoxicological impacts towards marine and estuarine bivalves. The selection of ENMs presented here was based on the OECD's Working Party on Manufactured Nanomaterials (WPMN), which involves the safety testing and risk assessment of ENMs. Physical-chemical characteristics and properties, applications, environmental relevant concentrations and behaviour in aquatic environment, as well as their toxic impacts towards marine bivalves are discussed. Moreover, it is also identified the impacts derived from the simultaneous exposure of marine organisms to ENMs and climate changes as an ecologically relevant scenario.